Efficiency of bus lane operation in Singapore - Nan Thein Gi Latt (2008)
This study has concentrated on the principal effect of bus lanes, which is on the traffic composition and flow of persons on the adjacent lanes. This was undertaken by initially collecting data at 3 bus lanes, covering the data such as traffic flows and occupancy rates for priority and non-priority vehicles.